Identification of the FDA‐Approved Drug Pyrvinium as a Small‐Molecule Inhibitor of the PD‐1/PD‐L1 Interaction. (29th June 2021) - Fattakhova, Elena; Hofer, Jeremy; DiFlumeri, Juliette; Cobb, Madison; Dando, Timothy; Romisher, Zachary; Wellington, Justin; Oravic, Michael; Radnoff, Madison; Patil, Sachin P.
Abstract: Immune checkpoint blockade involving inhibition of the PD‐1/PD‐L1 interaction has provided unprecedented clinical benefits in treating a variety of tumors. To date, a total of six antibodies that bind to either PD‐1 or PD‐L1 protein and in turn inhibit the PD‐1/PD‐L1 interaction have received clinical approvals. Despite being highly effective, these expensive large biotherapeutics possess several inherent pharmacokinetic limitations that can be successfully overcome through the use of low‐molecular‐weight inhibitors. One such promising approach involves small‐molecule induced dimerization and sequestration of PD‐L1, leading to effective PD‐1/PD‐L1 inhibition. Herein, we present the discovery of such potential bioactive PD‐L1 dimerizers through a structure‐ and ligand‐based screening of a focused library of approved and investigational drugs worldwide. Pyrvinium, an FDA‐approved anthelmintic drug, showed the highest activity in our study with IC50 value of ∼29.66 μM. It is noteworthy that Pyrvinium, being an approved drug, may prove especially suitable as a good starting point for further medicinal chemistry efforts, leading to design and development of even more potent structural analogs as selective PD‐1/PD‐L1 inhibitors. Furthermore, the adopted integrated virtual screening protocol may prove useful in screening other larger databases of lead‐ and drug‐like molecules for hit identification in the domain of small‐molecule PD‐1/PD‐L1 inhibitors. Abstract : The dimerizer : This study aimed to identify bioactive inhibitors of the PD‐1/PD‐L1 protein‐protein interaction for cancer immunotherapy. Pyrvinium, an FDA‐approved anthelmintic, showed promising activity (IC50 – 29.66 μM), thus presenting an immediate clinical potential against PD‐L1 expressing cancers. Pyrvinium may also act as a novel lead for development of more potent, selective PD‐1/PD‐L1 antagonists.